Evaluate the Current Expressions of Compression Strength and UPV Relationship - Altlomate, Abdelmajeed; shahidan, shahiron; Alatshan, Faesal; Elkher, Mohammed; Raihan Ramzi Hannan, Nurul Izzati; Mohd Zuki, Sharifah Salwa; Sheikh Khalid, Faisal; Wan Ibrahim, Mohd Haziman (International Journal of Integrated Engineering, 2018)
The ultrasonic pulse velocity method UPV has been commonly implemented to examine the mechanical properties and reliability of concrete structures. The principle of UPV is the speed of propagation of waves that depends on the density and the modulus of elasticity of the concrete. UPV is a simple and easier method of non-destructive testing (NDT) for evaluating the structures and material.Â Â The results can be rapidly achieved and data can be periodically collected from the same test points.[1] This paper aimed to evaluate the current mathematical relationships between the compressive strength and (UPV) for concrete samples. The current formulae assimilate limited numbers of experimental tests. This is because of the formula produced of these data is limited to the specimens were tested only. In this study, 575 different experimental tests between 3 and 180 days for compressive strengths ranging from about 20 to 100 MPa were collected and summarized. Moreover, the current equations have been developed to give an accurate correlation between Compressive strength and UPV. In addition, a contemporary design formula was presented